Rate control of cell sheet recovery by incorporating hydrophilic pattern in thermoresponsive cell culture dish. Issue 8 (2nd October 2013) - Kumashiro, Yoshikazu; Matsunaga, Teruyuki; Muraoka, Megumi; Tanaka, Nobuyuki; Itoga, Kazuyoshi; Kobayashi, Jun; Tomiyama, Yumiko; Kuroda, Masatoshi; Shimizu, Tatsuya; Hashimoto, Iwao; Umemura, Kazuo; Yamato, Masayuki; et al.
Abstract Thready stripe‐polyacrylamide (PAAm) pattern was fabricated on a thermoresponsive poly(N‐isopropylacrylamide) (PIPAAm) surface, and their surface properties were characterized. A PIPAAm surface spin‐coated with positive photoresist was irradiated through a 5 µm/5 µm or a 10 µm/10‐µm black and white striped photomask, resulting in the radical polymerization of AAm on the photoirradiated area. After staining with Alexa488 bovine serum albumin, the stripe‐patterned surface was clearly observed and the patterned surface was also observed by a phase contrast image of an atomic force microscope. NIH‐3T3 (3T3) single cells were able to be cultured at 37°C on the patterned surfaces as well as on a PIPAAm surface without pattern, and the detachment of adhered cells was more rapidly from the patterned surface after reducing temperature. Furthermore, the rate of detachment of 3T3 confluent cell sheet on the patterned surface was accelerated, compared with on a conventional PIPAAm surface under the static condition. The rate control of cell sheet recovery should contribute the preservations of cell phenotype and biological functions of cell sheet for applying to clinical trials. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2849–2856, 2014.